A Novel Index-based Assessment Method for Rural Homestead Utilization - Xu, Chengquan; Liu, Youwen; Jin, Shaofei (2022 International Conference on Automation, Robotics and Computer Engineering (ICARCE), 2022)
Due to the lack of basic data and long-term lack of scientific management of rural homestead in China, homestead construction shows great randomness and dispersion, and there is no centralized layout. Based on the recently completed Rural Cadastral and housing survey results, the paper constructs an index system for the evaluation of rural homestead utilization from three aspects: density dimension, functional dimension and social dimension. The index system includes building floor area ratio, residential unit density, three-dimensional center of gravity, homestead density, average building floors, proportion of public building area, one household multi residence rate and other indicators. The data on house bases in four different villages in Putian City, Fujian Province, including the island, the coastal plain area, the suburban hilly area and the mountainous area, are analyzed from the index system to analyze the current situation of rural homestead use and provide a scientific basis for the construction and management of homestead land.